HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA DAN TANGAN TERHADAP AKURASI SMASH BOLA VOLI ATLET PUTRA REKITA KOTO GASIB - Nailur Rizkiyah; Ni Putu Nita Wijayanti; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this study is that smash skills are still not good, this is seen when athletes do smash, the ball often does not cross the net and does not find the right target and doesn not generate points for the team. This is due the lack of accuracy in doing the smash because of the coordination of the eyes and hands is not yet maximal. This study aims to determine whether there is a relationship of wrist flextion and eyes and hands coordination to the accuracy of the volleyball smash of the male athlete Rekita Koto Gasib. Type this research is correlation to see the level of relationship between different variables. The sampling teachnique is the overall population (Total Sampling) of the volleyball athlete Rekita Koto Gasib men. The sample in this study was the male athlete Rekita Koto Gasib totaling 12 people. This research was conducted in the field of PT. KTU ASTRA Rekita Koto Gasib. The instrument used in this study were the wrist flextion test, eye and hand coordination test and the spike test. The result of the data in this study are smash. Analyzes were performed using multiple correlations. From the calculation result obtained by the multiple correltion coefficient (R test) obtained R count = 0.988 while Rtable obtained by 0,602, so Rcount>Rtable, proved to be a joint relationship between wrist flextion (X1) and eye and hand coordination (X2) to smash accuracy (Y).Key Words: Flexibility, Eye and Hand Coordination, Smash.